An Analisis Kepuasan Mahasiswa Terhadap Kualitas Layanan Sistem Informasi Akademik Fuzzy Servqual - Prasetio, Luky; Setiawan Assegaff; Kurniabudi (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2025)
This study aims to analyze student satisfaction with the quality of the Academic Information System (SIAKAD) services at Universitas Dinamika Bangsa using the Fuzzy Servqual method. The analysis is based on five service quality dimensions: Reliability, Responsiveness, Assurance, Empathy, and Tangibles. The defuzzification results indicate that the Reliability and Responsiveness dimensions have a GAP value of 0.0, signifying that the services provided meet student expectations. Meanwhile, the Assurance, Empathy, and Tangibles dimensions have a GAP value of 1.0, suggesting that students' perceptions of the service exceed their expectations. Thus, overall, students are satisfied with the services provided by the academic information system. Furthermore, this study identifies key factors influencing student satisfaction, including Assurance, which reflects security and trust in the system, Empathy, which demonstrates attentiveness and care for student needs, and Tangibles, which relate to the system's physical facilities and interface. The findings emphasize the importance of maintaining and optimizing service quality while ensuring that the Reliability and Responsiveness dimensions remain stable and do not decline over time. The recommendations derived from this study are expected to contribute to improving academic services and developing strategies to enhance student satisfaction at Universitas Dinamika Bangsa.